Social Media Performance Analysis: A Study of Follower Engagement on the Instagram Account @bukumurahanak - Anjari, Becik Gati; Permanasari, Kartika Indah; Ulya, Izzatul; Rochman, Fatkhur (PINISI Discretion Review, 2025)
Instagram is one of the main platforms in digital marketing, yet many business accounts still struggle to achieve optimal audience engagement. This study examines the Instagram account @bukumurahanak, which has more than 7,800 followers but records an engagement rate (ER) of only 1.2%, below the industry standard of 3–6%. The purpose of this research is to analyze the factors causing low engagement, evaluate the influence of content type on interaction, and propose improvement strategies. A quantitative descriptive method was applied through the analysis of 75 posts in 2024 and a survey of 200 respondents. ER was calculated to measure audience involvement based on impressions and follower count, while simple linear regression was used to test the influence of content type on engagement variation. The results show that interactive content achieved the highest reach, educational content was the most efficient, and promotional content performed the lowest (ER 0.9%). Regression analysis confirmed that content type significantly affects engagement (R² = 0.510), with 51% of the variation explained by content and 49% by other factors such as visual quality and posting consistency. In conclusion, content quality and relevance are critical in driving engagement. This study recommends balancing educational and interactive content while redesigning promotional content through storytelling, appealing visuals, and stronger calls-to-action.